Spanish Archaeology in the Near East in the Twentieth Century - Vidal, Jordi (Near Eastern archaeology, 2024)
The Spanish archaeological presence in the Near East was very scarce during most of the twentieth century. The excavations carried out at Shechem, Mogaret Dalal, El-Khiam, or Khirbet Arair were made possible by isolated efforts from outside the academic sphere. It was not until the 1980s that universities began to organize excavations and consolidate the Spanish presence in the region. The arrival of democracy, the reorganization of university research, and the availability of greater economic resources were the main elements that allowed this consolidation.